Colonel George Monro and the Defence of Fort William Henry, 1757 - Inglis, John (Proceedings of the Society of Antiquaries of Scotland, 1916)
The identification of the individual arose from the discovery of a document in the Register House, Edinburgh which was signed by " Alexander Monro of Auchinbowie and Captain George Monro of Brigadier Otway's Regiment of Foot, his brother-german." It is known that Otway's Regiment, the 35th Foot, now the Royal Sussex, formed the nucleus of the garrison at Fort William Henry, and Captain Monro's record of service in the manuscript Army List for 1752 shows that he is the Colonel Monro who was given the command of the regiment in 1750. An account of his life is presented along with a description of the fighting which is one of the best known incidents in American history.